Quality Factor and SNR Compensation of Free Space Optical Communication Link Using Different Modulators - Hammadi, Ali; Al-Askery, Ali; Zghair, Entidhar (International Journal of Engineering and Technology, 2018)
Free space optical (FSO) systems introduce the best solution for the broadband network requirements with a cost reduction compared to the optical wire communication systems. This paper, studies the signal to noise ratio (SNR) and quality factor (Q-factor) for using two types of modulation formats and compares their performance. The analysis are performed for Mach-Zehnder modulator (MZM) and electro-absorption modulator (EAM) with distance range (1-4) km of FSO by using avalanche photo-diodes (APD) receivers. The simulation results are obtained based on the Optisystem 7.0 with optical high data rate of 10 Gbs for this communication system. The simulation results have shown that MZM gives better performance compared to EAM for different ranges and for the selected beam divergence value